Hamlet Based on the Play by William Shakespeare - Shakespeare, William (Metrodome, 2003)
Arguably Shakespeare's greatest work, the tragedy of Hamlet's quest to admonish his uncle and seek revenge for his father's murder, remains a breathless, tense and endlessly rich tale that continues to enthrall and inspire. Kevin Klines adapts, stages and stars in this indelible production of Shakespeare's most famous play with a daring and depth few of his American contemporaries seem prepared to match. [www.play.com]